2007
DOI: 10.1055/s-2007-965580
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insight into the Regulation of GSH Biosynthesis in Higher Plants

Abstract: In higher plants, the redox-active tripeptide glutathione (GSH) fulfills a plethora of functions. These include its pivotal role for maintaining the cellular redox poise and its involvement in detoxification of heavy metals and xenobiotics. Intimately linked to these functions, GSH also acts as a cellular signal, mediating control of enzyme and/or regulatory protein activities, either directly or via glutaredoxins. The redox potential of the GSH/GSSG couple is not only affected by the GSH/GSSG ratio but also b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(49 citation statements)
references
References 78 publications
2
45
0
2
Order By: Relevance
“…AsA-GSH-cycle metabolism is an essential mechanism of plant resistance under stressful conditions [38,41]. Glutathione removes excess H 2 O 2 [42] and lipid peroxides keep ROS under control [43]. APX detoxifies H 2 O 2 into water using AsA as the major substrate where GSH continuously regenerates AsA from DHA, the oxidized form, via the AsA-GSH cycle.…”
Section: Discussionmentioning
confidence: 99%
“…AsA-GSH-cycle metabolism is an essential mechanism of plant resistance under stressful conditions [38,41]. Glutathione removes excess H 2 O 2 [42] and lipid peroxides keep ROS under control [43]. APX detoxifies H 2 O 2 into water using AsA as the major substrate where GSH continuously regenerates AsA from DHA, the oxidized form, via the AsA-GSH cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it could be assumed that sulphate supplied into soil led to an increase in the glutathione pool in T. cacao plant tissues; and the high pool of glutathione in tissues participates in the tolerance/resistance of cocoa genotypes (hybrids) to P. megakarya. This finding with T. cacao reminds the redox-active properties of glutathione (GSH/ GSSH) which fulfils protective functions when plants are exposed to biotic or abiotic stress (Rausch et al 2007). Moreover, Bloem et al (2004Bloem et al ( , 2007 reported that the infection of Brassica napus L. with Pyrenopeziza brassicae increased cysteine and glutathione contents, as well as the activity of l-cysteine desulfhydrase.…”
mentioning
confidence: 63%
“…Moreover, H 2 O 2 diffusion was shown to increase concomitantly with light intensity and time of illumination (Mubarakshina et al, 2010). Additional observations have suggested that glutathione, whose synthesis is affected by changes in photosynthesis, may also act as a plastid signal that controls expression of stress defense genes in the nucleus (Wachter et al, 2005;Mullineaux & Rausch, 2005;Rausch et al, 2007).…”
Section: Other Stress-response Programsmentioning
confidence: 97%